Correction: Morphogenesis of the C. elegans Intestine Involves Axon Guidance Genes. - Alparslan Asan; Stephan A Raiders; James R Priess (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1005950.].